Poligami dalam Surah an-Nisa' (4): 3 (Aplikasi Pendekatan Kontekstual Abdullah Saeed). - Faisal Haitomi; Masiyan M Syam (El-Afkar: Jurnal Pemikiran Keislaman dan Tafsir Hadis, 2020)
This article is motivated by the understanding of some people not to say everything about Surah an-Nisa '(4): 3 as one of the legitimacy of the practice of polygamy. This understanding is reinforced by the practice of polygamy carried out by the Prophet and the interpretation of the majority of scholars who provide a strong reason for the practice of polygamy. Some contemporary scholars try to reconstruct this understanding by approaching the Qur'an contextually. This article uses Abdullah Saeed's contextual approach as the lens of analysis to find the main purpose of the verse. As a result, the writer found that sura 4: 3 is not a verse that emphasizes the practice of polygamy, but rather emphasizes caring for orphans and doing justice to others. In line with the main purpose of the verse, then in the context of Indonesia, marrying them (orphans in the interpretation of Al-Tabari and other classical scholars. While according to Muhammad Syahrur, Nashr Hamid Abu Zayd is an orphan's parent) is not a way to give a sense of security and protection for them, because the state has guaranteed freedom and security for orphans and women with the presence of KPAI and KOMNAS for women and there are many institutions and organizations that are concerned with caring for orphans.